STUDY ON ARTS, HANDICRAFTS AND DANCES OF THE KUTIA KANDHA TRIBE OF KANDHAMAL DISTRICT IN ODISHA - Mallick, Sunil; Mohapatra, Ratnakar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The aim of paper is to highlight the traditional arts, handicrafts and dances of the Kutia Kandhas of Kandhamal District in the state of Odisha. The Kutia Kandha, a primitive tribe primarily belongs to the Kandhamal district areas like Balliguda sub-Division, Tumudibandha Block area, Gumma, Belghar and Bilamala and Jhiripani Gram panchayats. The people of Kutia Kandha tribe live in the hilly region and identify unique culture and customs. The art form has a deep cultural significance for the Kutia Kandha people, who view it as a way to preserve their traditional way of life and express their cultural identity. The research delves into the unique art forms, traditional crafts and vibrant dance practices that are integral to the Kutia Kandhas’ way of life. Through ethnographic research methods, this study documents and analyses the symbolic meanings, social functions and the processes of preservation and transformation of these cultural expressions in the context of modern influences. The findings aim to contribute to the understanding of the Kutia Kandhas’ cultural identity and the broader discourse on indigenous art and traditions. The study employs a qualitative research approach, primarily using ethnographic methods. Fieldwork was conducted in various villages within Kandhamal District, where participant observation, in-depth interviews and visual documentation were utilized to gather data. The participants include tribal elders, artisans and performers who provided insights into the traditional practices. Additionally, archival research was conducted to compare historical records with current practices. Data analysis was done through thematic coding, focusing on recurring patterns and cultural motifs in the art, crafts and dances of the Kutia Kandhas of Kandhamala in Odisha.